A Comprehensive Examination of Workforce Diversity - Gharti, Amit; Modi, Devendra Kumar (International Research Journal of MMC, 2024)
Workforce diversity has become a crucial topic in organizational management due to its significant effects on workplace dynamics, innovation, and performance. Although our understanding of diversity has grown, its comprehensive impact across various sectors and organizational settings is still not fully understood. This review aims to integrate current knowledge on the many sides of workforce diversity, assess its challenges, and explore opportunities for boosting organizational effectiveness. This study performed a thorough 32 literatures using Nepal Journals Online (NepJOL), an online publication of Nepalese journals, targeting publications from January 2019 to May 2024. Search terms included "workforce diversity," "diversity in organizations," and "cultural diversity," among others. The selection included studies that assessed the effects of diversity using both qualitative and quantitative approaches. The review highlights mixed findings on the correlation between workforce diversity and organizational performance, emphasizing the complexity of diversity's impact. Key themes include the importance of inclusive workplace cultures, challenges in multicultural communication, gender representation issues, and knowledge gaps in diverse sectors. Analysis of publication trends reveals a growing recognition of diversity's significance, particularly in recent years. Workforce diversity is crucial for organizational success, yet its impact varies across contexts. Prioritizing inclusive workplace cultures and addressing diversity-related challenges are essential. Future research should focus on longitudinal studies, sector-specific investigations, and innovative approaches to promote diversity and inclusion. Embracing diversity as a strategic asset can drive innovation and sustainable growth in diverse global environments.